Research and practice of SASE cloud security - Chaoyang YE; Xin WANG; Shicong ZHANG; Zhiyong ZHAN; Yisha LIU (Dianxin kexue)
With the development of the Internet today, earth shaking changes have taken place compared with the traditional network.In today's network reform, ＆quot;cloud＆quot; has become the mainstream direction of the evolution of enterprise IT architecture, so the requirements for cloud security are becoming higher and higher.The practical deployment scheme of SASE cloud security architecture was introduced to solve the problem of cloud security for customers.A unique and complete SASE solution was proposed, which combined security functions with SD-WAN functions, and realized real-time monitoring, intelligent analysis and automatic interception of malware or malicious activities by building a unified management and control platform and centralized deployment of core security resource pool.Practice has proved that the scheme achieves the expected results in unified management and control, intrusion detection and defense, fine access control and so on, and can fully ensure the cloud security of enterprises.